Rett syndrome in a pediatric patient: progressive clinical presentation and genetic confirmation via mecp2 mutation - Salazar Lozano, Hugo Esteban; Pérez León, Ana Karina; Pérez León, María Daniela; Pérez León, Andrea Carolina; Atapuma Madrid, Diego Fernando (Arandu UTIC, 2025)
Rett syndrome (RTT) is a rare X-linked neurodevelopmental disorder characterized by an early phase of apparently normal development, followed by rapid regression in language, motor coordination, and purposeful hand use. We report the case of a female pediatric patient with classic RTT confirmed by a de novo pathogenic mutation in the MECP2 gene. The patient developed typically until 18 months of age, when she began to lose speech, motor function, social interaction, and developed stereotypic hand movements. Initially misdiagnosed with autism spectrum disorder and cerebral palsy, genetic testing ultimately provided definitive diagnosis. The clinical picture included motor apraxia, epilepsy, axial hypotonia, respiratory dysautonomia, gastrointestinal dysfunction, and neurocognitive impairment. Despite intensive multidisciplinary care—physical, occupational, speech and respiratory therapy—along with adjunct treatments like cannabidiol and ozone therapy, her condition progressively deteriorated. She died at age 9 years and 9 months from rhinovirus pneumonia and acute respiratory failure. This case highlights the diagnostic delays commonly associated with RTT in resource-limited settings and underscores the importance of early clinical suspicion, prompt MECP2 testing in cases of developmental regression, and comprehensive multidisciplinary management. It also demonstrates the crucial role of family support in preserving quality of life. This report contributes to the clinical literature by offering a complete view of the classical RTT trajectory and reinforcing the urgent need for public health policies ensuring genomic access and long-term specialized care for rare neurodevelopmental conditions.